ESPERANÇAS E DECEPÇÕES Uma análise crítica da Prática Pastoral do neopentecostalismo na Igreja Internacional da Graça de Deus sob a perspectiva da Práxis Religiosa - Romeiro, Paulo Rodrigues (2004)
This text analyses the Neo-Pentecostal practices in the International Church of the Grace of God. This church has substantially expanded in Brazil, gathered an enormous number of followers and obtained marked visibility in the media. The research studies the historical trajectory of Neo-Pentecostalism, its development in Brazil, and theological aspects of the movement. The text also presents the Church of Grace, its origins, theology, governmental structure, pastoral ministry and expansion. Due to its insertion in Neo-Pentecostalism, the Church of Grace reflects a theology that proposes to ban sickness, poverty and all types of suffering from human life, in order to produce a new generation of believers: rich and healthy. According to this theology, Christians should live their lives free of any negative aspect of human existence. If this does not happen, it is because of a lack of faith, being in the power of Satan, or exhibiting behaviors that do not please God. As such, the mark of a true Christian is physical and emotional health, as well as financial prosperity. Nonetheless, Neo-Pentecostal preaching has produced disappointments, principally when physical cure does not occur, and financial riches do not appear. This thesis formulates a practical pastoral proposal that offers hope to those deceived by this triumphant message, with aims to return to Christian life within the space of Christian faith.(AU)